Antioxidant and Antibacterial Activities of Trigonella foenum graecum Leaves - Singh, Aklavya Kumar; Singh, Aklavya Kumar; Kaur, Avneet; B, Shrivastava; Lamba, Hardarshan Singh; Sharma, Pankaj; Sodhi , Jaspreet Kaur (International Journal of Psychosocial Rehabilitation, 2020)
Trigonella foenum graecum (Fenugreek) is one of the known traditional and most promising medicinal herbs belonging to the Leguminosae family. It is used as a vegetable, spice and a medicinal plant. Since antioxidant properties have been linked to health benefits of natural products, such property was studied in fenugreek leaves. The antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) was studied. Also the study was aimed to investigate the in vitro antibacterial activity of Trigonella foenum graecum leaves extract against Staphylococcus aureus using agar disc diffusion method. The results indicated that the ethanolic extract Trigonella foenum graecum leaves possess antioxidant activity and thus can be a significant source of natural antioxidants. Also the hot (boiling) water extraction of fenugreek leaves contain active ingredients that have an inhibitory effect on the growth of Staphylococcus aureus.